2004
DOI: 10.2118/04-07-04
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation and Ignition Behaviour of Saturated Hydrocarbon Samples With Crude Oils Using TG/DTG and DTA Thermal Analysis Techniques

Abstract: This research is aimed at providing a better understanding of the oxidation behaviour of fractions of crude oil, and to then develop an approach to improve ignition for air injection processes. In this research, Thermogravimetric and Differential Thermal Analysis (TG/DTA) techniques were used to investigate oxidation behaviour using thermal fingerprinting effects on pure paraffin samples and mixtures of pure components with crude oil. The results demonstrated that each paraffin sample shows d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 8 publications
(11 reference statements)
1
15
0
Order By: Relevance
“…Figure 3a shows the TG/DTG curves of oil in dynamic air purge under different heating rates condition, and Figure 3b on the other hand, illustrates the DSC curves of oil in dynamic air purge under different heating rates condition, In Figure 3a, it is observed that the TG pattern of heating rate at 15°C/min is different with heating rates are 5 and 10°C/min. For 5 and 10°C/min, as the heating rates increase, the curve slightly shifts to a higher temperature region and this phenomenon is in consistence with Downloaded by [University of Sussex Library] at 08:00 28 June 2016 Thomas (2001), Sonibare et al (2003), and Li et al (2004). Also, in Figure 3b it is observed that the exothermic peaks shift from a lower temperature region to a higher temperature region along with the incLensement of heating rates.…”
Section: Define Oxidation Reaction Stagessupporting
confidence: 62%
See 1 more Smart Citation
“…Figure 3a shows the TG/DTG curves of oil in dynamic air purge under different heating rates condition, and Figure 3b on the other hand, illustrates the DSC curves of oil in dynamic air purge under different heating rates condition, In Figure 3a, it is observed that the TG pattern of heating rate at 15°C/min is different with heating rates are 5 and 10°C/min. For 5 and 10°C/min, as the heating rates increase, the curve slightly shifts to a higher temperature region and this phenomenon is in consistence with Downloaded by [University of Sussex Library] at 08:00 28 June 2016 Thomas (2001), Sonibare et al (2003), and Li et al (2004). Also, in Figure 3b it is observed that the exothermic peaks shift from a lower temperature region to a higher temperature region along with the incLensement of heating rates.…”
Section: Define Oxidation Reaction Stagessupporting
confidence: 62%
“…The success of an air injection process (AIP) process depends mainly on the crude oil and rock properties as well as the operational conditions (Li et al, 2004). Theoretically, the combustion of oil can be initiated whenever oxygen comes in contact with fuel.…”
Section: Introductionmentioning
confidence: 99%
“…The authors conclude that high oxygen injection rates are required to stimulate the scission reactions. Germain et al [20] describe combustion tube tests with light oil in heterogenous low permeability (1 − 100 mD) reservoirs using pressures of 40 − 45 bars and leading to combustion temperatures between 260 • C and 370 • C. Low pressure thermal gravity and differential scanning calorimetry test results [36] show that distillation is a dominant process for the recovery of light and medium oils at elevated temperatures. This may indicate that pressure effects need to be taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…However, both the main components involved in the LTO reaction and the differences associated with the oxidation characteristics among different components have not been well understood. To quantify the oxidation characteristics of crude oils, thermal analysis such as thermogravimetric analysis and differential scanning calorimetry (TG‐DSC), pressure differential scanning calorimetry (PDSC), and thermogravimetric analysis coupled with Fourier transform infrared spectrometer (TG‐FTIR) have been applied to investigate the oxidation properties of crude oil and its SARA fractions, as summarized in Table . Also, this table tabulates the reaction modes and characteristics during the combustion of light and heavy oils, the kinetics and thermochemical parameters of each reaction mode, the differences of oxidation characteristics between light, medium, and heavy oils, the oxidation relationship of crude oil and SARA fractions during the combustion process, and the combustion process of asphalt binder and its SARA fractions, respectively.…”
Section: Introductionmentioning
confidence: 99%